2018
DOI: 10.1093/jas/sky166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent feeding of tylosin phosphate during the finishing period on feedlot performance, carcass characteristics, antimicrobial resistance, and incidence and severity of liver abscesses in steers1

Abstract: Liver abscesses (LA) are a source of economic loss for feedlot cattle feedlots, and the 2017 veterinary feed directive has restricted further use of tylosin phosphate to prevention and control of LA. Our objective was to evaluate effects of intermittent tylosin phosphate feeding on incidence and severity of LA in feedlot cattle and presence of total antimicrobial-resistant Enterococcus spp. Steers (n = 312, 411.4 ± 6.71 kg) were blocked by initial BW and randomly assigned to a treatment group. Treatments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Beukers et al () suggested that early withdrawal of tylosin prior to slaughter contributed to a lower proportion of macrolide‐resistant enterococci. Additionally, Müller et al () noted that the environment where cattle are raised, namely where antibiotics have previously been used, seemed to play a large role in the presence of macrolide‐resistant enterococci. Interestingly E. faecium is also worthy of investigation as a probiotic, due to its tolerance of bile acids and its antagonistic effects towards intestinal pathogens; specifically, it harbours bacteriocins active against Gram‐positive foodborne pathogens, such as Listeria monocytogenes (Izquierdo et al ) .…”
Section: Introductionmentioning
confidence: 99%
“…Beukers et al () suggested that early withdrawal of tylosin prior to slaughter contributed to a lower proportion of macrolide‐resistant enterococci. Additionally, Müller et al () noted that the environment where cattle are raised, namely where antibiotics have previously been used, seemed to play a large role in the presence of macrolide‐resistant enterococci. Interestingly E. faecium is also worthy of investigation as a probiotic, due to its tolerance of bile acids and its antagonistic effects towards intestinal pathogens; specifically, it harbours bacteriocins active against Gram‐positive foodborne pathogens, such as Listeria monocytogenes (Izquierdo et al ) .…”
Section: Introductionmentioning
confidence: 99%
“…They observed a reduction in macrolide resistance, just prior to and after the removal of tylosin. Müller et al (17) explored the intermittent use (1 week on, 2 weeks off) of tylosin compared to continuous or no tylosin and found no difference in Ery R enterococci between tylosin treatment at each time point. However, these researchers did record a higher percentage of Ery R enterococci with increasing days on feed between day 20 and day 118.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the administration of tylosin may coselect for enterococci with resistance to tetracycline, even in the absence of tetracycline use (45). Müller et al (17) reported increased proportion of Tet R enterococci in cattle feces with increasing days on feed, but found no relationship between Tet R occurrence and the administration of tylosin in feed. Although tetracycline was absent in the diet, Müller et al (17) observed an initially high proportion of Tet R enterococci in cattle feces at approximately 10% on day 0, with increases between day 20 (∼20%) and day 118 (∼40%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other FDA requirements pertaining to how antibiotics must be administered may actually drive up drug use in practice. For example, a recent study found that intermittent feeding of tylosin achieves reduction of liver abscesses in cattle comparable to continuous feeding, but this strategic antibiotic use may violate laws governing specific use practices . Given the regulations on antibiotic use, veterinarians may be required to administer higher doses than they feel is necessary, or for longer than needed, to prevent disease…”
Section: Assessing Antibiotic Use In Animal Agriculturementioning
confidence: 99%